The psychological and social consequences of single-sided deafness in adulthood. (2nd January 2018) - Lucas, Laura; Katiri, Roulla; Kitterick, Pádraig Thomas
Abstract: Objectives: This study examined the subjective psychological and social effects of highly asymmetric hearing loss (single-sided deafness [SSD]) in adults. Design: Three group interviews were conducted using the critical incident technique and analysed using an inductive thematic analysis. Study sample: Eight adults with a clinical diagnosis of a moderately severe hearing loss or greater in one ear and normal or near-normal hearing in the other ear. Results: A range of functional hearing difficulties associated with SSD including impaired speech in background noise and reduced spatial awareness were reported to affect social and psychological well-being. Social consequences of SSD resulted from activity limitations and participation restrictions including withdrawal from and within situations. Participants reported psychological effects including worrying about losing the hearing in their other ear, embarrassment related to the social stigma attached to hearing loss and reduced confidence and belief in their abilities to participate. Conclusions : Single-sided deafness can be associated with many negative consequences. Counselling may help overcome the psychological consequences of hearing loss regardless of whether technological support such as a hearing aid is prescribed. The audiological management of these individuals should support the development of listening strategies and set appropriate expectations for participation in everyday listening situations.